Relationship between P2XR4 Gene Variants and the Risk of Schizophrenia in South-East of Iran: A Preliminary Case-Control Study and in Silico Analysis - Milad Heidari Nia; Mahdieh Jafari Shahroudi; Ramin Saravani; Saman Sargazi; Mahdiyeh Moudi; Azizollah Mojahed (Tehran University of Medical Sciences, 2021)
Background: Schizophrenia (SZN) is a heterogeneous disorder. Recently, the role of purinergic receptor's signaling in mental disorders has implicated. There is no evidence regarding the association of P2XR4 single nucleotide polymorphisms (SNPs) and the risk of behavioral disorders. Therefore, this preliminary study, we determined the association of rs1169727A/G and rs25644A/G variants located in P2XR4 gene with the risk of SZN. Methods: This case-control study was performed on 150 SZN patient referring to Baharan Hospital, Zahedan (Eastern of Iran) in 2018. Genotyping was done by tetra-amplification refractory mutation system polymerase chain reaction (Tetra ARMS-PCR). Different databases were used to determine the effects of the SNPs on the secondary structure of P2XR4 pre-mRNA and protein as well as binding of transcriptional regulators. Results: The G allele of rs1169727 significantly increased the risk of SZN (OR=1.41, 95%CI=1.02-1.93, P=0.039), but there was no significant association was found between the other SNP and SZN. Moreover, GG model of rs1169727 (OR=2.46, 95%CI= 1.32-4.62, P=0.004) and rs25644 (OR=3.45, 95%CI= 1.12-5.10, P=0.013) increased the risk of SZN. The substitution of A and G alleles of rs1169727 significantly altered the secondary structure of pre-mRNA (P=0.1). In silico analysis revealed that rs25644A/G could act as an intronic cryptic donor site. Screening for flanking sequence of rs1169727A/G and rs25644A/G predicted a novel enhancer and silencer for both SNPs. Conclusion: rs1169727A/G and rs25644A/G are linked to SZN susceptibility in a sample of the Iranian population. In-silico analysis indicated that rs25644 have substantial roles in determining the pre-mRNA and protein structure of P2XR4 gene.